2003
DOI: 10.1177/0898264303251893
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Older Adults’ Capacity for Medication Management in a Self-Medication Program

Abstract: The direct effects of cognition and medication regimen complexity were important predictors of medication management capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 24 publications
5
85
0
Order By: Relevance
“…1 Failure to achieve and sustain adequate dose levels has been linked to poor outcomes in various areas of medicine, and the Academy of Managed Care Pharmacy (AMCP) and National Committee for Quality Assurance (NCQA) have recently recommended that suboptimal dosing be considered in monitoring pharmaceutical care in Medicare Part D beneficiaries. [2][3][4][5] The probability of reaching and sustaining an approved dose is affected by the complexity and convenience of dosing, 6,7 how the benefit and side-effects of the medication are managed by clinicians, 6 as well as a number of patient and environmental factors, such as the cognitive abilities of the patient, 8,9 availability of caregiver support, and the affordability of the treatment. 6 The characteristic declines in learning and memory seen in AD may erode the patient's ability to adhere to medication regimens with or without caregiver support.…”
mentioning
confidence: 99%
“…1 Failure to achieve and sustain adequate dose levels has been linked to poor outcomes in various areas of medicine, and the Academy of Managed Care Pharmacy (AMCP) and National Committee for Quality Assurance (NCQA) have recently recommended that suboptimal dosing be considered in monitoring pharmaceutical care in Medicare Part D beneficiaries. [2][3][4][5] The probability of reaching and sustaining an approved dose is affected by the complexity and convenience of dosing, 6,7 how the benefit and side-effects of the medication are managed by clinicians, 6 as well as a number of patient and environmental factors, such as the cognitive abilities of the patient, 8,9 availability of caregiver support, and the affordability of the treatment. 6 The characteristic declines in learning and memory seen in AD may erode the patient's ability to adhere to medication regimens with or without caregiver support.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that cognitive decline is an independent risk factor for medication mismanagement [7,8] . However, studies focusing specifically on problems with medication management as an indicator of cognitive function are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic conditions (e.g., depression, dementia) that affect cognition abilities of elderly people are associated with problems in medication self-management [75]. Forgetting to take medication is a frequent problem [76].…”
Section: Discussionmentioning
confidence: 99%